Produção e avaliação de probiótico de bactérias lácticas crescida em vinho para a alimentação de suínos recem-desmamados e adultos. - Flavio Henrique Ferreira Barbosa (2010)
The healthful and nutritional food production in high amount it has become a challenge for all the professionals who work with all the food productive chain. The world-wide swine production grew and Brazil had a significant increase in swine meat exportations. So that the activity of swine production keeps productive, with the generation of profits, growthpromoters have been incorporated to feeds to improve the digestive process and the performance of the animals, by increasing weight and reducing diseases. However, in recent years the awareness on the use extreme of these products has increased, as well as become evident the possible upheavals for health of these animals and of the man, asconsequences of this promoters. The available alternatives for substitution of antimicrobials include probiotics, prebiotics, symbiotics and phytotherapeutics. Concerning importance are well known Sucroalcooleiro System Agroindustrials (SAG) in Brazil, its social,economic and politic. The increase of the alcohol production causes a problem for the environment, due to vinasse prodution, residue produced in great volume. Following this line, this work considered to carry through the prospection of probiotics microorganisms and to use vinasse discarded in the plants of alcohol and stills of cachaça as vehicle orway of culture for microorganisms in probiotics formularizations to be used in performance of swine. For the gotten results, it was possible to evaluate and to evidence, that the base of vinasse for the feeding of monogastric animals (swines) just-been born and finished ispossible to produce a probiotic preparation of lactic bacteria. Verifying itself in this in case that, until the present moment, that the improvement of the processes of cellular multiplication in vinasse aiming at to the maximum productivity the acceptable costs for its production on a large scale becomes necessary. Lactic bacteria can be used for use asprobiotic using as criterion its capacity of survival and growth in vinasse, leaving evident, at some moments, the limited possibility of other applications as the fertirrigação due to the raised value of DBO reached in the liquid residue after-culture of Lactobacillus due to obligator substances addition to the cellular multiplication. In function of the gotten results, it was concluded that the studied probiotic did not present significant differences on the too much treatments tested in swine, even so was evidenced not the existence of decurrent problems of the consumption of vinasse and that in the tests of colonization of thegastrointestinal treatment, of adhesion, antagonism in vitro and ex vivo, antimicrobial susceptibility and histopathology examinations, the results if show promising and reflect the necessity of new tests in the future.